Correction of optical distortion by image processing (2004)
The invention is a camera comprising the following. A camera that is capable of reducing distortion from an optical system has an optical system that is configured to capture a wide field of view of a subject. An image sensor and circuitry are coupled to the optical system and are configured to convert the output of the optical system to electrical signals suitable for use by an image processing circuit. The image processing circuit is coupled to the image sensor and is configured to reduce optical distortions from the combination of the optical system and the image sensor where the correction includes reference to a table of parameters held in a solid-state memory, attached to said image processing circuit, wherein the table of parameters may be specific to the particular combination of said optical system and said image.